Electronic structure of CoSi2 films on Si(111) studied using time-resolved two-photon photoemission - Kutschera, Michael; Groth, Tilman; Kentsch, Carsten; Shumay, Igor; Weinelt, Martin; Fauster, Thomas (Journal of Physics: Condensed Matter, 2009)
The occupied and unoccupied electronic structure of thin epitaxial CoSi2 films grown on Si(111) substrates was studied using time-resolved two-photon photoemission and valence-band photoemission spectroscopy. The work function of the sample surfaces and the Schottky barrier height at the metal-semiconductor interface were measured as a function of annealing temperature. The photoemission data reveal several occupied and unoccupied electronic states which exhibit a high sensitivity to the annealing temperature. Time-resolved measurements show a behavior typical for a short-lived hot-electron gas and indications for an image-potential resonance.